Analisis Daya Dukung dan Strategi Pengembangan Ekowisata di Mentari Ocean View, Kabupaten Pacitan - Ikhwa Muazulfa, Tsalatsun; Sunarto, Sunarto; Kusumaningrum, Lia (Jurnal Forest Island, 2025)
Tourism activities in forest areas can potentially disrupt the balance of forest ecosystems. The existence of tourist visits needs special attention in terms of the environment. At a certain time when environmental conditions have exceeded their carrying capacity, there will be instability in environmental conditions that have an impact on environmental damage. The purpose of this study is to determine the carrying capacity of ecotourism in Mentari Ocean View in supporting tourism activities, analyze the potential of Mentari Ocean View ecotourism in achieving sustainable tourism, and formulate a strategy for the development of Mentari Ocean View ecotourism. The research methods used are primary surveys and secondary surveys. The data that has been obtained is analyzed using qualitative and quantitative descriptive methods. The results obtained in the study are that the value of the physical carrying capacity, real carrying capacity, and effective carrying capacity of Mentari Ocean View has not been exceeded, the assessment of the ecotourism potential of Mentari Ocean obtained an overall potential value index of 86.73% which means that it is high or suitable for development, the main priority of the development strategy is the environmental aspect centered on controlling environmental damage and utilizing the potential of natural resources, the second economy is centered on increasing business opportunities and increasing ecotourism branding, and the third is social, which is centered on improving the quality of human resources and local government support..